Isolation of MRSA from Drinking water Supplies in Al-Anbar Province, Iraq (Medico Legal Update, 2020)
This study was aimed to isolate MRSA from water supplies from different places in alanbar province, fifty water samples were cultured on nutrient, macConkey and blood agars then subcultured on MSA and Staph 110, then gram stain and biochemical test done to confirm this bacteria. Then antibiotic susceptibility test were done on S. aureus by using different antibiotics including Methicillin, erythromycin, Doxycycline, Sulfa-trimethoprim, penicillin, chloramphenicol, ciprofloxacin.The results showed that 12 (24%) samples were diagnose as S. aureus, these were showed complete resistance to methicillin, erythromycin, Doxycycline and showed different percent for resistance to other antimicrobials that used.In conclusion, the MRSA were isolated from drinking water in significant percentage and this strain of bacteria were showed higher resistance to antibiotics.